Automatic AMR Generation for Simple Sentences Using Dependency Parser. (2016) - Paul, N. Pelja; Revathy, P.; Sini, G.M.; Binu, R.
Abstract: Information retrieval is an important task in the field of natural language processing. Retrieving information requires a basic representation at the sentence level. Representation for sentences with same meaning should be same so that we can claim that the representation seems to be good enough to use in various natural language tasks. AMR is such a semantic representation aimed at large-scale human annotation inorder to built a giant semantic bank. In this paper, we present an automatic AMR tool for simple sentences with the help of dependency parser.